Risk factors for cardiometabolic health in Ghana: Cardiometabolic Risks Study Protocol-APTI Project - Hormenu, Thomas; Salifu, Iddrisu; Antiri, Ebenezer Oduro; Paku, Juliet Elikem; Arthur, Aaron Rudolf; Nyane, Benjamin; Ableh, Eric Awlime; Gablah, Augustine Mac-Hubert; Banson, Cecil; Amoah, Samuel; Ishimwe, Marie Consolatrice Sage; Mugeni, Regine (Frontiers in Endocrinology, 2024)
Introduction: Cardiometabolic diseases are rapidly becoming primary causes of death in developing countries, including Ghana. However, risk factors for of Cardiometabolic diseases, including obesity phenotype, and availability of cost-effective diagnostic criteria are poorly documented in an African-ancestry populations in their native locations. The extent to which the environment, occupation, geography, stress, and sleep habits contribute to the development of Cardiometabolic disorders should be examined.The overall goal of this study is to determine the prevalence of undiagnosed diabetes, prediabetes, and associated cardiovascular risks using a multi-sampled oral glucose tolerance test.The study will also investigate the phenotype and ocular characteristics of diabetes and prediabetes subgroups, as well as determine if lifestyle changes over a one-year period will impact the progression of diabetes and prediabetes.The study employs a community-based quasi-experimental design, making use of pre-and post-intervention data, as well as a questionnaire survey of 1200 individuals residing in the Cape Coast metropolis to ascertain the prevalence and risk factors for undiagnosed diabetes and prediabetes. Physical activity, dietary habits, stress levels, sleep patterns, body image perception, and demographic characteristics will be assessed. Glucose dysregulation will be detected using oOral glucose tolerance test, fasting plasma glucose, and glycated hemoglobin.Liver and kidney function will also be assessed. Diabetes and prediabetes will be classified using the American Diabetes Association criteria. Descriptive statistics, including percentages, will be used to determine the prevalence of undiagnosed diabetes and cardiovascular risks. Inferential statistics, including ANOVA, and t-tests, chi-square tests, ROC curves, logistic regression, as well asand linear mixed model regression will be used to analyze the phenotypic variations in the population, ocular characteristics, and glycemic levels, the sensitivity levels of diagnostic tests, etiological cause of diabetes in the population, and effects of lifestyle modifications, respectively. Additionally, t-tests will be used to assess changes in glucose regulation biomarkers after lifestyle modifications.Ethics and dissemination: Ethics approval was granted by the Institutional Review Board of the University of Cape Coast, Ghana (UCCIRB/EXT/2022/27). The findings will be disseminated in community workshops, online learning platforms, academic conferences and submitted to peerreviewed journals for publication.